2014
DOI: 10.1007/s00167-014-3181-4
|View full text |Cite
|
Sign up to set email alerts
|

Does flexible tunnel drilling affect the femoral tunnel angle measurement after anterior cruciate ligament reconstruction?

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Eight included studies 9 , 15 , 16 , 20 , 21 , 23 , 33 , 35 quantified femoral tunnel positioning by utilizing radiologic parameters. No studies reported any significant difference in the intra-articular femoral tunnel aperture location.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight included studies 9 , 15 , 16 , 20 , 21 , 23 , 33 , 35 quantified femoral tunnel positioning by utilizing radiologic parameters. No studies reported any significant difference in the intra-articular femoral tunnel aperture location.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, many of the studies directly comparing the use of AM-FR and AM-RR have contained a low level of evidence and differed in the radiographic modality used for assessment. Specifically, several included studies 15 , 23 , 33 , 35 utilized radiographs for evaluation of tunnel positioning and measurement, which may be less accurate than other modalities of advanced imaging (see Table 1 ). Therefore, further study is required to more clearly define the anatomic or radiologic differences that result from the use of these 2 methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the complexity of the knee motion and soft tissue balancing of living subjects, data from actual ACL reconstruction may have more direct clinical relevance than the data from the operation using in-vitro cadaveric knee models. [ 11 , 12 ] Therefore, the aim of the present study is to compare the femoral tunnel characteristics using a rigid versus flexible reamer during single-bundle ACL reconstruction using a transportal technique. To accomplish this aim, we reconstructed three-dimensional (3D) knee models based on the in-vivo computerized tomography (CT) images of the operated knee from the patients who had undertaken the single-bundle ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%